A Self‐Separating Multiphasic System for Catalytic Hydrogenation of CO2 and CO2‐Derivatives to Methanol. Issue 22 (26th October 2022) - Diehl, Thomas; Lanzerath, Patrick; Franciò, Giancarlo; Leitner, Walter
Abstract: Catalytic conversion of CO2 and hydrogen to methanol was achieved in a self‐separating multiphasic system comprising the tailor‐made complex [Ru(CO)ClH(MACHO‐C12 )] (MACHO‐C12 =bis2‐[bis(4‐dodecylphenyl)phosphino]ethylamine) in n ‐decane as the catalyst phase. Effective catalyst recycling was demonstrated for the carbonate and the amine‐assisted pathway from CO2 to methanol. The polar products MeOH or MeOH/H2 O generated from the catalytic reactions spontaneously formed a separate phase, allowing product isolation and catalyst separation without the need for any additional solvent. In the amine‐assisted hydrogenation of CO2, the catalyst phase was recycled over ten subsequent runs, reaching a total turnover number to MeOH of 19200 with an average selectivity of 96 %. Abstract : Phase separation : Ru‐catalyzed hydrogenation of dimethylcarbonate or CO2 to methanol was accomplished in n ‐decane using the new alkyl‐tagged MACHO‐C12 nonpolar ligand. During the reaction, the polar products MeOH or MeOH/H2 O naturally separate in a second phase. In the amine‐assisted hydrogenation of CO2, the catalyst phase was recycled for 10 times, reaching a total turnover number to MeOH of 19200.